Contrasting drivers of community‐level trait variation for vascular plants, lichens and bryophytes across an elevational gradient. (6th October 2019) - Roos, Ruben E.; van Zuijlen, Kristel; Birkemoe, Tone; Klanderud, Kari; Lang, Simone I.; Bokhorst, Stef; Wardle, David A.; Asplund, Johan
Abstract: Across environmental gradients, community‐level functional traits of plants can change due to species turnover, intraspecific variation and their covariation. Studies on vascular plants suggest that species turnover is the main driver of trait variation across gradients, although intraspecific variation can also be important. However, there is limited knowledge about whether this holds for non‐vascular primary producers such as lichens and bryophytes. We hypothesized that intraspecific variation is more important for non‐vascular than for vascular primary producers because they lack specialized structures to maintain homeostasis and should therefore be more responsive to extrinsic factors. To assess the relative importance of species turnover versus intraspecific variation for vascular plants, lichens and bryophytes, we estimated species abundance and measured chemical (tissue nitrogen (N) and phosphorous (P) content, N:P ratio and pH) and non‐chemical (specific leaf or thallus area, dry matter content and water holding capacity) functional traits along an elevational gradient in alpine southern Norway. We calculated community‐weighted mean traits and quantified the relative contribution of species turnover, intraspecific variation and their covariation to total trait variation across the gradient. We found mixed support for our hypothesis: the contribution of intraspecific variation to total trait variation for N and N:P was higher in lichens than in vascular plants and bryophytes, but in general the contribution of intraspecific variation differed among functional traits and producer groups. Nutrient variables (N, P and N:P) were significantly impacted by intraspecific variation for vascular plants and lichens but not for bryophytes. Non‐chemical traits and pH were mainly driven by species turnover effects in all primary producer groups. Our results highlight that while nearly all studies on primary producer trait variation across environments have focused on vascular plants, trait variation of other largely neglected but ecologically important producer groups, such as lichens and bryophytes, may show very different responses to the same environmental factors. In order to fully understand how future environmental changes impact on community‐ and ecosystem‐level processes, traits of primary producers other than vascular plants—and their within‐species variation—need to be considered in systems where these groups are abundant. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.